2022
DOI: 10.3389/fimmu.2022.883287
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of at-Risk Individuals on Preventive Intervention for Rheumatoid Arthritis: A Mini Review

Abstract: There has been intense research focus on the biological mechanisms underlying the transition from health to disease for rheumatoid arthritis (RA) over recent years, and it is now well established that a state of autoimmunity precedes the development of symptoms for a large proportion of patients. This has led to an increased interest in the identification of at-risk groups and the potential for preventive intervention. The ability of several immunomodulatory agents to delay or prevent RA is under investigation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Future studies will show if this new ACPA also has functional capacities. Plasma cell survival niches in the joint were found present already at time of RA diagnosis supporting the notion that such structures are attractive therapeutic targets in RA 45 or even individuals at risk of developing RA 46 , 47 .…”
Section: Discussionmentioning
confidence: 63%
“…Future studies will show if this new ACPA also has functional capacities. Plasma cell survival niches in the joint were found present already at time of RA diagnosis supporting the notion that such structures are attractive therapeutic targets in RA 45 or even individuals at risk of developing RA 46 , 47 .…”
Section: Discussionmentioning
confidence: 63%
“…14 15 While preventive interventions for RA could reduce patient burden and societal cost at scale, few studies have quantified the preferences of at-risk groups for risks and benefits of treatments to reduce the chance of developing RA. Previous qualitative studies have found that the acceptability of preventive approaches for RA is influenced by perceptions of treatment effectiveness and harms, 16 but there are limited examples of studies to quantify the relative importance of treatment attributes, benefit-risk trade-offs and preference heterogeneity. 17 One study eliciting preferences for preventive treatments for RA which used profile-case best-worst scaling 18 had a relatively small sample size and did not report acceptable benefit-risk trade-offs.…”
Section: What This Study Addsmentioning
confidence: 99%
“…In SLE, rheumatoid arthritis and type 1 diabetes (T1DM) the presence of disease-specific autoantibodies prior to clinical disease manifestation is well-established (6)(7)(8)(9)(10). This is less well characterized for autoantibodies targeting BP180 or BP230, which characterize and cause bullous pemphigoid (14).…”
Section: From Health To Autoimmunitymentioning
confidence: 99%